Interactive planning and control for finished vehicle logistics - Marit Hoff-Hoffmeyer-Zlotnik; Susanne Schukraft; Dirk Werthmann; Stephan Oelker; Michael Freitag (Digitalization in Maritime and Sustainable Logistics: City Logistics, Port Logistics and Sustainable Supply Chain Management in the Digital Age. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 24, 2017)
Logistic processes on sea and inland ports play an important role in the context of finished vehicle logistics as the vehicles are turned over for import and export here. Due to increasing dynamics and complexity, the planning and control of these processes requires high flexibility and reactivity. For example, changing dealer demands or delays of trucks, trains and ships may require a short-term replanning of the logistics processes on sea and inland ports. In this context, this paper describes the procedures and challenges within finished vehicle logistics. Furthermore, an approach for developing highly flexible and efficient logistics planning and control processes for sea and inland ports is introduced. On the one hand, this approach involves an interactive planning tool that visualizes the outcomes of different planning alternatives computed by discrete event simulation. On the other hand, a concept for a novel control system for order allocation will be presented that is based on tracking and tracing of vehicles and workers. This includes a novel method for tracking and tracing as current methods are not suitable in terms of accuracy or cost-efficiency. It is envisioned that the introduced concept will offer significant improvements in terms of reactiveness to spontaneous changes and efficiency in travel paths compared to current practices.
urn:nbn:de:gbv:830-88217766; 10419/209193; https://econpapers.repec.org/RePEc:zbw:hiclpr:24
Keywords: 650; maritime; port logistics; port transshipment